Dietary Total Antioxidant Capacity and Gastric Cancer: A Case-Control Study - Saba Narmcheshm; Fatemeh Toorang; Bahareh Sasanfar; Maryam Hadji; Ahmadreza Dorosty Motlagh; Kazem Zendehdel (Journal of Nutrition and Food Security)
Background: Gastric cancer (GC) is the most common cancer among Iranian men. A diet rich in antioxidant compounds has been offered as an appropriate strategy for reducing the risk of GC. This study aimed to determine the possible association between dietary total antioxidant capacity (dTAC) and the Iranian population's GC risk. Methods: In total, 178 newly diagnosed GC patients and 238 healthy controls were recruited for this hospital-based case-control study. Dietary intakes were collected using a validated 146-item diet history questionnaire (DHQ), and dTAC was analyzed using Ferric reducing antioxidant potential (FRAP) assay. Results: The mean value of dTAC was 10.42±5.42 for cases and 11.42±5.86 for controls. Black tea, fruits, and cereals consumption were the main contributors to dTAC in both groups. DTAC was associated with a reduction in the risk of GC (OR 0.54; 95%CI: 0.31–0.92) (second vs. lowest tertile). This association did not change after adjustment for body mass index, education, energy intake, smoking, and Helicobacter pylori infection (0.55; 95% CI: 0.31-0.99). There was no significant association between fruits, vegetables, nuts, and legumes TAC with GC. Conclusion: The whole intake of dTAC from different food sources was not high in the population; however, this amount showed a preventive effect against GC.